Perception and retrospection: The dynamic consistency of responses to survey questions on wellbeing - Stephen Pudney (Centre for Microdata Methods and Practice (cemmap), 2010)
Implementation of broad approaches to welfare analysis usually entails the use of 'subjective' welfare indicators. We analyse BHPS data on financial wellbeing to determine whether reported current and retrospective perceptions are consistent with each other and with the existence of a common underlying wellbeing concept. We allow for adjustment of perceptions in a vector ARMA model for panel data, with dependent variables observed ordinally and find that current perceptions exhibit slow adjustment to changing circumstances and retrospective assessments of past wellbeing are heavily contaminated by current circumstances, assessments of past wellbeing are heavily contaminated by current circumstances, causing significant bias in measures of the level and change in welfare.
Keywords: C23; C25; C33; C35; D84; 330; financial wellbeing; perceptions; dynamic adjustment; BHPS; Zufriedenheit; Messung; Reichtum; Sozialer Indikator; ARMA-Modell; Großbritannien